Unified behavior of soot production and radiative heat transfer in ethylene, propane and butane axisymmetric laminar diffusion flames at different oxygen indices. (1st November 2016) - Escudero, F.; Fuentes, A.; Consalvi, J.-L.; Liu, F.; Demarco, R.
Highlights: Measurements of soot volume fraction and temperature in axisymmetric laminar diffusion flames. Optical technique to measure simultaneously soot volume fraction and temperature. Effects of oxygen index and fuel sooting propensity on soot production and radiative loss. Scaling analysis based on the smoke point height to unify the sooting and radiative behaviors. Abstract: An experimental study was conducted to investigate the effects of oxygen index on the flame geometry, soot production and radiative loss in laminar over-ventilated co-flow buoyant axisymmetric diffusion flames at atmospheric pressure. Three gaseous hydrocarbon fuels, namely ethylene, propane, and butane, were considered. The oxygen index was varied from 21% to 37% and several mass flow rates were used. These conditions were chosen to keep the flames under the smoke point. Soot volume fraction and temperature were deduced from line-of-sight attenuation and two-color emission measurements, respectively. A scaling analysis based on the smoke point height was developed in order to unify the sooting behavior of the flames investigated. This analysis produced correlations for the flame height, the maximum soot volume fraction, the maximum integrated soot volume fraction and the radiant fraction at the smoke point.